2005
DOI: 10.1073/pnas.0503081102
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent pollen-tube growth in pistils of alders ( Alnus )

Abstract: In alders, where fertilization occurs Ϸ8 weeks after pollination, the pollen tube (male gametophyte) grows intermittently in four steps in close association with the development of the ovary and its ovules. Pollen tubes stop growing in the style, at the ovarian locule, and at the chalaza (ovule), before reaching an embryo sac for fertilization. At the stage when the ovary develops an ovule primordium in each of the two locules, many pollen tubes germinate on the stigma, and a few of them reach the style, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 33 publications
(24 reference statements)
4
33
0
Order By: Relevance
“…This increase in the rate of growth was previously reported in other species including Petunia [15], peach [9], kiwifruit [50], and apricot [70]. Pollen tube growth in the style also appears to be faster than in the ovary [11,71], and these differences have been related to the requirement for maturation of ovary structures. The acceleration of pollen tube growth rate in the style could be due to developmental events within the pollen tube itself, such as the deposition of the first callose plug, the completion of mitosis II, or by an internally programmed shift to heterotrophic growth.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This increase in the rate of growth was previously reported in other species including Petunia [15], peach [9], kiwifruit [50], and apricot [70]. Pollen tube growth in the style also appears to be faster than in the ovary [11,71], and these differences have been related to the requirement for maturation of ovary structures. The acceleration of pollen tube growth rate in the style could be due to developmental events within the pollen tube itself, such as the deposition of the first callose plug, the completion of mitosis II, or by an internally programmed shift to heterotrophic growth.…”
Section: Discussionsupporting
confidence: 77%
“…The pollen tube traverses different tissues within the pistil on its path to the embryo sac, and the recorded pollen tube growth rate is faster in the style compared to the stigma or the ovary [8,9]. As observed in different species such as peaches [10] or alders [11], slow growth in the ovary has been related to stops and decelerations resulting from the wait for particular structures -the obturator or the ovules- to become receptive to the pollen tube. Indeed, male–female synchrony appears to be a prerequisite for successful fertilization [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, before entering the ovary, PT guidance requires intensive communication with the surrounding sporophytic maternal tissues, and the presence of the FG seems not to be necessary for the largest part of the PT's journey [2][3][4]. However, after exit from the TT tissue and emergence on the surface of the placenta, PT guidance is thought to be primarily under gametophytic control, although the maternal sporophytic Key words: Arabidopsis, maize, micropyle, pollen tube guidance, signalling, synergid, Torenia.…”
Section: Introductionmentioning
confidence: 99%
“…Pollen tubes can grow through the stigma and style even in a pistil that lacks a female gametophyte (Hülskamp et al, 1995). This has been demonstrated in a semi-in vitro system using a cut pistil from which the ovary was removed (Higashiyama et al, 1998) and occurs in plants where megasporogenesis occurs after pollination (Sogo and Tobe, 2005). These results suggest that the female gametophyte is not necessary for pollen-tube guidance from the stigma to the base of the style in many species.…”
Section: Signaling In Sporophytic Guidancementioning
confidence: 58%